Sources of Occupational Wage Differentials in a « Competitive » Labour Market - Bruce, C.; Cheslak, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1978)
The authors present a survey of the wage-setting practices of a number of employers of clerk-typists in the city of Calgary to provide additional information concerning the determinants of extra-market wage differentials.